2017
DOI: 10.1177/0020764017705895
|View full text |Cite
|
Sign up to set email alerts
|

Facebook addiction and loneliness in the post-graduate students of a university in southern India

Abstract: With the rapid growth of popularity and user-base of Facebook, a significant portion of the individuals are susceptible to develop addictive behaviors related to Facebook use. Loneliness is a factor which influences addiction to Facebook.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
63
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(76 citation statements)
references
References 25 publications
2
63
0
1
Order By: Relevance
“…In another study done in the same campus on postgraduate students by Shettar et al; showed that 26 % of students had facebook addiction and also showed that there is a positive correlation between severity of Facebook addiction and extent of experience of loneliness. [17] Based on the cutoff values for SAS-SV given by Kwon et al; for males more than 31 and females more than 33, smartphone addiction was present in 36% of the students. This is similar to the results of Indian meta-analysis on assessment of smartphone addiction by Davey et al; which showed 39-44%(6).…”
Section: Discussionmentioning
confidence: 99%
“…In another study done in the same campus on postgraduate students by Shettar et al; showed that 26 % of students had facebook addiction and also showed that there is a positive correlation between severity of Facebook addiction and extent of experience of loneliness. [17] Based on the cutoff values for SAS-SV given by Kwon et al; for males more than 31 and females more than 33, smartphone addiction was present in 36% of the students. This is similar to the results of Indian meta-analysis on assessment of smartphone addiction by Davey et al; which showed 39-44%(6).…”
Section: Discussionmentioning
confidence: 99%
“…After retrieving and evaluating the full texts, 28 articles did not meet our criteria. At the end of the screening process, 13 articles met all the inclusion and exclusion criteria and were recruited in this systematic review (Anil et al, 2016;Bhogle, 1991;Grover et al, 2019Grover et al, , 2018Malhotra et al, 2019;Mishra et al, 2013;Nayyar and Singh, 2011;Ninan and Gopinath, 2013;Samanta et al, 2012;Shettar et al, 2017;Singh and Mishra, 2009;Susheela et al, 2018;Upmanyu et al, 1994).…”
Section: Study Selectionmentioning
confidence: 99%
“…Most (n = 4) studies were conducted in Karnataka (Anil et al, 2016;Ninan and Gopinath, 2013;Shettar et al, 2017;Susheela et al, 2018), followed by Punjab (n = 3) Nayyar and Singh, 2011;Upmanyu et al, 1994), Andhra Pradesh (n = 2) (Bhogle, 1991;Mishra et al, 2013), Delhi (n = 1) (Singh and Mishra, 2009), Haryana (n = 1) (Malhotra et al, 2019), and West Bengal (n = 1) (Samanta et al, 2012). A study by Grover et al included participants from multiple states of India (Grover et al, 2018).…”
Section: Study Characteristics and Instrumentsmentioning
confidence: 99%
See 2 more Smart Citations